Light Emitting Diodes Photobiomodulation Improves Cardiac Function by Promoting ATP Synthesis in Mice With Heart Failure - Zhang, Wenwen; Gao, Xinlu; Wang, Xiuxiu; Li, Desheng; Zhao, Yiming; Zhang, Tingting; Ne, Jingwen; Xu, Binbin; Li, Shuainan; Jiang, Zuke; Sun, Hongyue; Ma, Wenya; et al. (Frontiers in Cardiovascular Medicine, 2021)
Heart failure (HF) is the final stage of various cardiovascular diseases, often leading to severe cardiac output deficits with a high morbidity and mortality. In recent years, light emitting diodes-based therapy (LEDT) has been widely used in multiple cardiac diseases, while its modulatory effects on cardiac function in patients with HF still remain unclear. Therefore, the objective of this study was to investigate the effects of LED-Red irradiation on cardiac function in mice with HF and to reveal its mechanisms. In this study, we constructed a mouse model of HF by permanent ligation of the left anterior descending coronary artery (LAD). We found that LED-Red (630-650 nm) was an effective wavelength for the treatment of HF. Meanwhile, the application of LED-Red therapy (630- 650 nm, 3 mW/cm2) to treat HF mice enhanced cardiac function, diminished the ratio of heart weight/body weight and heart weight/tibia length, as well as inhibited myocardial fibrosis. In addition, LED-Red therapy attenuated the extent of perivascular fibrosis. Mechanistically, it was revealed that LED-Red irradiation enhanced cardiomyocytes contractility by promoting ATP synthesis, which resulting in a significant increase in calcium transients and cell shortening.